Silica/Clay Organo-Heterostructures to Promote Polyethylene-Clay Nanocomposites by in Situ Polymerization - Zapata-Ramirez, P (2013)
Two clay organo-heterostructures have been prepared and employed as fillers and catalyst supports for the development of polyethylene-clay nanocomposites. The new silica-clay organo-heterostructures have been obtained from two organoclays modified with tetramethoxysilane. In contrast to related heterostructures reported previously the organic moieties are not removed by heating and their presence intends to confer hydrophobicity to the interlayer region of the clay, even after delamination by hydrolysis-polymerization of the alkoxysilane takes place. These organo-heterostructures were used for preparing clay-polyethylene nanocomposites by in situ polymerizations in which the organo-heterostructures were added together with the metallocene catalyst, and by using the silica-clay as support for the metallocene catalysts. The polymers formed when the organo-heterostructures were used as support for the catalyst have higher molecular weights than the standard polyethylene formed under homogeneous conditions. Moreover, the presence of the inorganic silica network developed in the interlayer region of the organoclay favours the existence of a larger organophilic region in which it is possible to accommodate both the catalyst and the monomer, and hence when the polymer grows in this environment it can assist in the exfoliation of the clay layers inside the polyethylene matrix. The polymer particle morphology improved with the presence of the clay in the polymerization. The molecular weight for support systems presented an increasing ca. 40% compared to neat PE, and by TEM it was found that the clay layers were well dispersed in the PE matrix. © 2012 Elsevier B.V.